DOES ETHICAL CONSTRAINT AFFECTS PORTFOLIO PERFORMANCE? EVIDENCE FROM UK SRI BOND FUNDS - Mensah, Andy (2011)
ABSTRACT More and more investors are increasingly incorporating their ethical principles and values into their investment decisions. This has driven the growth of the SRI industry consistently over the past two decades. This raises questions on whether the application of ethical screening enhances or harms portfolio performance. The remarkable growth of the SRI industry has triggered several empirical studies that seek to investigate on the impact of ethical screening on portfolio performance. Despite the growth in academic interest in SRI, little evidence have been provided on the performance of SRI bond funds as the empirical literatures have largely focused on SRI equity funds. Little attempt has been made to assess the performance of UK SRI bond funds. This study therefore extend the literature in the fixed-income area by evaluating the performance of 11 UK SRI bond funds to a matched sample of conventional bond funds of similar characteristics in terms of age, size and investment scope. Since there is lack of consensus on the best model to explain the variations in bond fund returns, I consider several performance attribution models to ensure robustness of results. Using single and multi-index performance attributions models in addition to Sharpe and Treynor’s performance appraisal ratios, my findings overall suggests that there is no significant difference in the performance of the SRI bond unit trusts and conventional bond unit trusts. The single and multi-index models predominantly resulted in positive but insignificant alphas for both SRI and the conventional bond funds. While the results of the multi-index models indicates that conventional bond funds marginally outperformed the SRI bond funds in many instances, the results from the Sharpe and Treynor’s index favours the SRI bond funds over its corresponding peers in terms of performance.